Understanding the Role and Challenges for Indigenous and Community-Governed Lands in Contributing to Target 3 of the Global Biodiversity Framework - Caroline Lumosi; Carolina Hazin; James Fitzsimons; Siyu Qin (Land)
Target 3 of the Kunming-Montreal Global Biodiversity Framework commits nations to protecting and conserving at least 30% of the world’s terrestrial and inland water areas and coastal and marine areas by 2030 (30 × 30). There can be significant overlap with Indigenous and traditional territories (ITTs) and protected areas. We explore if and/or how ITTs are currently recognized and reported as contributors to national protection targets by analyzing whether these territories are counted as standalone conservation areas, integrated into government-led protected and conserved area networks or systems, or neither, in 18 countries. Our analysis reveals critical linkages between tenure regimes, ITTs and their recognition in reporting to global area-based conservation databases. Legal recognition of tenure rights, particularly ownership and stewardship rights, emerged as the strongest predictor of whether ITTs are formally being accounted for in these databases. Our findings also reveal that the contribution of ITTs to national protection targets not only depend on tenure type but also on governance rights, despite the way it is reported. We categorize systemic barriers and opportunities that have implications for the contribution of ITTs to 30 × 30 goals.